2009
DOI: 10.1080/00981380802451160
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Obesity and Coronary Heart Disease in People with Intellectual Disabilities

Abstract: Advances in health care for people with intellectual disabilities (ID) that have resulted in increased longevity also force health care providers, researchers, and policymakers to question the adequacy of chronic disease management for the growing number of middle aged and elderly persons in this population. We report on sociodemographic and clinical factors associated with obesity, hypertension, hypercholesterolemia, and diabetes mellitus in an ethnically/racially diverse sample of people with ID in New York … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…Our findings show that women were more likely to be overweight, obese, and have abdominal obesity than men. These sex-based differences are similar to those documented in smaller scale studies conducted in the USA, UK, and South Africa, 1,2,19,22,23 and two larger studies from the USA 28,32 and an earlier international study with Special Olympics participants. 10 The logistic regression analyses also revealed that age was a significant predictor of overweight, obesity, and abdominal obesity.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Our findings show that women were more likely to be overweight, obese, and have abdominal obesity than men. These sex-based differences are similar to those documented in smaller scale studies conducted in the USA, UK, and South Africa, 1,2,19,22,23 and two larger studies from the USA 28,32 and an earlier international study with Special Olympics participants. 10 The logistic regression analyses also revealed that age was a significant predictor of overweight, obesity, and abdominal obesity.…”
Section: Resultssupporting
confidence: 69%
“…Similarly, the proportion of women with WC levels indicative of abdominal obesity was significantly higher among women than men (χ 2 = 5.93, df = 1, p =.015). and United States and Canada; 1,25,26 our data generally show lower levels of overweight/obesity. However, we found similar levels of overweight (BMI ≥ 25) compared to previous studies of Special Olympics participants who were not from the USA 10,27 or Europe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%